The BBQ & campfire recipe book / Luke Cox - Cox, Luke
The BBQ & campfire recipe book contains dozens of recipes, from Old Favourites to something a bit more adventurous that'll get your tastebuds going when you head for the great outdoors this summer. Practical, full of useful hints and chock-a-block with great grub.